The Effect of Object-Oriented Physics Learning on Students' Abilities to Interpret and Make Reasoning about Data - Suryadi Suryadi; I Ketut Mahardika; Sudarti Sudarti; Supeno Supeno (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop students' abilities in interpreting and making reasoning about physics data. The type of research used is experimental research. Physics learning was carried out in two classes: control and experimental groups. In the experimental group, physics learning was oriented to student activities where students dealt with physics objects. In contrast, in the control group, physics was taught conventionally by applying direct learning. The ability to interpret and to make reasoning about data was obtained through written tests conducted on pre-test and post-test. Analysis of research data was carried out by qualitative descriptive and t-test statistical analysis. The descriptive analysis was performed to describe students' abilities to interpret and to make reasoning about data. A statistical t-test analysis was conducted to determine the difference in the impact of treatment on the two groups. The results showed that the average ability to interpret data and to make reasoning about data in the experimental group was 76.91 and 76.99, respectively, while in the control group, it was 53.33 and 63.08, respectively. The results of the t-test analysis showed that the 2-way (t-tailed) significance value was 0.000 < 0.05, so it could be stated that there was a difference in ability between the control group and the experimental group. Based on the results of these studies, it can be noted that learning physics that involves a lot of student activities that interact directly with physics objects can improve the skills of high school students in interpreting and reasoning scientific data.